C and O Isotopes of the middle and upper Tamengo Formation (Corumbá Group - Upper Ediacaran): effects of the sedimentary facies and diagenesis - Montenegro Rivera, Laura Carolina (2019)
The Tamengo Formation holds important and well preserved sedimentological and paleontological records of Upper Ediacaran Period. Previous works had centred on Corcal Mine, Saladeiro (now Sobramil Port) and Laginha Sections. However, there is no reports of detailed sedimentological and geochemical surveys on those and other outcrops of the Tamengo Formation at Corumbá-Ladário escarpment located at Paraguay River margins where the paleontological occurrences are concentrated. In the aim of contribute to the understanding of the paleo-environmental conditions, paleontological occurrences and its relationship at Tamengo Formation, detailed stratigraphic columns, description and interpretation of sedimentary facies, sampling, petrography, C and O isotope analysis along with other geochemical analysis were carried out on Corcal Mine, Sobramil Port and six new sections located along the Escarpment. From the obtained data, eight different facies and its C isotope signature were recognized: Wavy Bedding Mudstone (mean \'delta 13C, PDB\' =3.83%o PDB), Hummocky/Cross-Stratified Wackestone (mean \'delta 13C, PDB\' =3.98%o PDB), Cloudina Grainstone (mean \'delta 13C, PDB\' =4.36%o PDB), Intraclastic Packstone-Grainstone (mean \'delta 13C, PDB\' =4.19%o PDB), Low-Angle Cross-Laminated/Laminated Wackestone (mean \'delta 13C, PDB\'=4.93%o PDB), Cloudina Packstone (mean \'delta 13C, PDB\' =4.74%o PDB), Pelite, and Reworked Volcanic Tuff Facies, in which the Formation was dated by other authors, yielding an approximated age of 542 Ma. Also, very well-preserved C and O isotopic signatures were recognized. The carbon isotope data reveal more positive \'delta 13C, PDB\' values on coarser facies (Grainstone, Wackestone, Packstone) and in the calcareous beds overlying the Pelite facies, conforming six main distinctive patterns for carbonate facies that match with coarsening upwards cycles composing the Tamengo Formation. A ramp context of sedimentation has been interpreted for the Tamengo Formation, under strong storms influence, with a progressive tendency towards more positive \'delta 13C, PDB\' values from the deepest to shallower facies. A mid to outer ramp context was inferred for the Ladário-Corumbá, Goldfish, Sobramil and lower part of the Corcal Mine sections, with a mean \'delta 13C, PDB\' value of 3.97%o. For the mid part of the ramp two settings were interpreted; bioclastic lens represented by the Cloudina Grainstone and Intraclastic Packstone-Grainstone Facies and subcoastal setting, represented by the Low-Angle Cross-Laminated/Laminated Wackestone and Cloudina Packstone Facies with mean \'delta 13C, PDB\' values of \'delta 13C, PDB\' =4.33%o and \'delta 13C, PDB\' =4.87%o respectively, represented in the middle and upper part of the Corcal Mine Section. Also, the commonly addressed distribution of Cloudina and Corumbella on different facies could be the reflex of the oscillation between storms and fair-weather conditions; periodic influence of storm-waves or even typhoons in the ramp could avoid Cloudina fixation promoting constantly reworking and accumulating the shells on carbonate facies, while Corumbellas, probably restricted to deepest part of the ramp, expanded to the shallow parts of the ramp on fair weather conditions between storms, as settling by decantation of the Pelite Facies take place at the ramp, explaining the typic distribution of Cloudina restricted to carbonate facies and Corumbella to the interbedded Pelite Facies.